2020
DOI: 10.1590/2175-7860202071018
|View full text |Cite
|
Sign up to set email alerts
|

Flora do Ceará, Brasil: Begoniaceae

Abstract: Resumo Apresentamos o levantamento florístico de Begoniaceae no estado do Ceará, como parte do projeto Flora do Ceará: conhecer para conservar. O estudo baseou-se na análise de caracteres morfológicos de espécimes depositados nos herbários ALCB, EAC, HUEFS, HUVA, MBM, MBML, RBR e SP, complementada com bibliografias especializadas e análise de imagens de coleções-tipo. No estado, Begoniaceae está representada por quatro espécies do gênero Begonia: B. convolvulacea, B. humilis, B. reniformis e B. saxicola. As es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In addition, it is worth noting that the number of species indicated for the flora of Ceará (BFG 2018; Flora do Brasil 2020 under construction) is incomplete. Recent studies linked to the "Flora of Ceará Project: knowing to conserve" have shown how much the floristic diversity of that state is underestimated, confirmed with quotes from new records (Capistrano & Loiola 2015;Tabosa et al 2016;Rocha et al 2018;Lima et al 2018Lima et al , 2020Sampaio et al 2019a) or description of new species (Loiola 2013;Souza et al 2016;Sampaio et al 2016Sampaio et al , 2019bRibeiro et al 2017).…”
Section: Introdutionmentioning
confidence: 86%
“…In addition, it is worth noting that the number of species indicated for the flora of Ceará (BFG 2018; Flora do Brasil 2020 under construction) is incomplete. Recent studies linked to the "Flora of Ceará Project: knowing to conserve" have shown how much the floristic diversity of that state is underestimated, confirmed with quotes from new records (Capistrano & Loiola 2015;Tabosa et al 2016;Rocha et al 2018;Lima et al 2018Lima et al , 2020Sampaio et al 2019a) or description of new species (Loiola 2013;Souza et al 2016;Sampaio et al 2016Sampaio et al , 2019bRibeiro et al 2017).…”
Section: Introdutionmentioning
confidence: 86%
“…The most up-to-date works include those for Argentina (Delfini, 2017), Cuba (Calzado, 2000), the Dominican Republic (Burt-Utley, 1991), Ecuador (Smith & Wasshausen, 1986), Mesoamerica (Burt-Utley, 2015) and Brazil (in progress) (Jacques & Gregório, 2020). Additionally, there are further regional works available for Brazil, for example Bahia (de Souza Gregório et al, 2016), Serra do Brigadeiro State Park (Delfini & Souza, 2016), Ceará (Lima et al, 2020), Macaé de Cima Ecological Reserve (Jacques, 1996) and Serra dos Carajás (Kollmann, 2016); for Mexico (Nova Galiciana;Burt-Utley & McVaugh, 2001); and for Venezuela (Venezuelan Guyana; Steyermark, 1997). Recently, some illustrated popular guidebooks have been published, covering Arunachal, India (Morris, 2017), China (Shui & Chen, 2017), Borneo (Kiew et al, 2015) and Asia (Hughes et al, 2018b), which have a broad appeal but also are useful in aiding identification, particularly when images are included of the type or from the type locality.…”
Section: Current State Of Begonia Taxonomy and Future Needsmentioning
confidence: 99%